Practicality And Effectiveness Game Snake Chemistry Ladder as a Learning Media on Material Reaction Reduction and Oxidation Class X SMA/MA - Yusi Yuliana; Iswendi Iswendi (Universitas Riau, 2023)
Study this is study advanced with a development model Plomp done by Adelina and Iswendi (2021) with title development game snake ladder chemistry as a learning medium on material reduction and oxidation as well as nomenclature compound class X SMA/MA which is already valid, however Not yet tested level practicality and level its effectiveness. Objective study for disclose level practicality and level effectiveness game snake ladder chemistry as a learning medium on material Reaction Reduction and Oxidation class X MAN 1 Padang Panjang.Design study is One-Group Pretest-Posttest Design. Subject study is class X MIPA 3. Instruments study on test practicality form questionnaire practicality to teachers and participant educate and test effectiveness form question pre-test and completed post - test tested try it. Practicality data analyzed with percentage and effectiveness data with N-Gain. Based on results analysis of the data obtained mark teacher practicality is 91% (very practical) and participant educate on test small group by 86% (very practical), and test field-test obtained by 87% (very practical). Results analysis effectiveness obtained mark N-Gain by 76% with category effective. Based on results study can concluded that game snake ladder chemistry as a learning medium on material reaction reduction and oxidation class X MAN 1 Padang Panjang very practical and effective.